Literary reading strategies in the literacy process: contributions to the formation of readers - Goulart, Ilsa do Carmo Vieira (2024)
We start from the premise that reading is a permanent process of interaction between reader and text, in which the subjects rely both on certain purposes that guide the reading and on their previous knowledge and experiences, in order to produce meanings and effectively understand the texts. In this perspective, the research aims to identify how literary reading, from the proposal of strategies, can contribute to the process of reading comprehension of children in the literacy phase. For this, the proposed investigation is configured in a participatory research, of qualitative approach and of descriptive character, taking as technical and investigative procedure the systematic observation, from the application of reading activities, during the school year of 2022, in a class of the 1st year of elementary school, of a school of the municipal network, located in Campo das Vertentes, Minas Gerais. As a theoretical basis, we highlight the studies of Solé (1998) regarding reading strategies and Girotto and Souza (2010) regarding strategies specifically directed to literary reading. The results of the research reveal the importance of planning pedagogical actions that favor literary reading strategies in an educational context, as such stimuli contribute to the process of reading comprehension by children, significantly favoring the formation of autonomous, critical and reflective readers.